2005
DOI: 10.1007/s11206-005-4102-6
|View full text |Cite
|
Sign up to set email alerts
|

Race and Loss of Privilege: African American/White Differences in the Determinants of Job Layoffs From Upper-Tier Occupations

Abstract: Data from the Panel Study of Income Dynamics supports predictions from the minority vulnerability thesis concerning the determinants of job layoffs among African Americans and Whites who work in upper-middle-class occupations. Specifically, after controlling for seniority, layoffs for AfricanAmericans are relatively unstructured by traditional stratification-based causal factors, namely, background socioeconomic status, human-capital credentials, and job/labor market characteristics. Analyses also indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 40 publications
5
70
0
2
Order By: Relevance
“…Such scholarship relates firing to employers' willingness to undertake discretionary and arguably discriminatory behavior especially when unemployment is high and fired workers can be easily replaced (in these regards, see especially Donohue and Siegelman 1991). The prevalence of discriminatory firing is also consistent with recent work suggesting that employer subjectivity and biases make minorities especially vulnerable to forced exits (McBrier and Wilson 2004;Wilson and McBrier 2005). Firing includes discharge, constructive discharge, layoffs, and involuntary retirement, as well as other employer acts which effectively encourage the employee to quit, such as suspensions or failure to recall.…”
Section: Discriminatory Forms and The Explication Of Processsupporting
confidence: 81%
See 2 more Smart Citations
“…Such scholarship relates firing to employers' willingness to undertake discretionary and arguably discriminatory behavior especially when unemployment is high and fired workers can be easily replaced (in these regards, see especially Donohue and Siegelman 1991). The prevalence of discriminatory firing is also consistent with recent work suggesting that employer subjectivity and biases make minorities especially vulnerable to forced exits (McBrier and Wilson 2004;Wilson and McBrier 2005). Firing includes discharge, constructive discharge, layoffs, and involuntary retirement, as well as other employer acts which effectively encourage the employee to quit, such as suspensions or failure to recall.…”
Section: Discriminatory Forms and The Explication Of Processsupporting
confidence: 81%
“…In fact, as corporations experienced downsizing in the 1990s, African American white-collar workers were disproportionately displaced into lower-level white-collar and, particularly, blue-collar jobs, while whites benefited from traditional protective factors such as higher SES, professional or technical employment, union membership, and firm tenure (McBrier and Wilson 2004). This supports a "minority vulnerability thesis"-the flip side to the particularistic mobility argument-wherein downward mobility for minorities is more general, less circumscribed, and less predicted by traditional protective factors (see especially Wilson and McBrier 2005).…”
Section: Stratification Race and The Labor Marketmentioning
confidence: 52%
See 1 more Smart Citation
“…Although very few studies exist comparing actual discrimination patterns between the sectors (e.g., Hoffnar & Greene, 1996;Long, 1975;Wilson & McBrier, 2005), many studies have investigated discrimination trends within each sector, with the vast majority of these studies focusing on the public sector.…”
Section: Proposed Theoretical Differencesmentioning
confidence: 99%
“…Other work has found that the relationship between educational attainment and layoffs varies by race (Wilson and McBrier 2005). 3 The little research available on higher education suggests that a postgraduate degree insulates white women in white collar occupations from downward mobility more than American or Hispanic women (Wilson 2009).…”
Section: Human Capital Theory Education and Occupational Attainmentmentioning
confidence: 99%